The Impact of English Medium Instruction (EMI) on Primary Classes in Private Schools - Iffath, M.I.R.F.; Paranthaman, V. (Faculty of Arts University of Jaffna, Sri Lanka, 2025)
This study investigates the impact of English Medium Instruction (EMI) on primary school students in private schools in the Chilaw area. It examines the influence of EMI on children’s cognitive skills, English language competence, and overall academic achievement. The primary aim is to identify the factors contributing to the success of EMI programs and to propose strategies for enhancing both their effectiveness and equity. A review of existing literature indicates that EMI can significantly strengthen students’ cognitive development and English language proficiency. However, it also highlights challenges and disadvantages, particularly for learners from diverse socioeconomic backgrounds. This research seeks to provide a comprehensive understanding of the overall impact of EMI on primary education by integrating findings from multiple perspectives. A mixed-methods approach was adopted, combining quantitative data from pilot and standardized tests with qualitative data from surveys, interviews, and classroom observations. The sample included parents, teachers, and students from private schools in the Chilaw area. Data analysis identified trends, challenges, and success factors in EMI adoption. The findings reveal that addressing socioeconomic disparities and incorporating both English and native languages into the curriculum are essential for fostering an inclusive and supportive learning environment. Furthermore, active parental involvement, curriculum adaptation, and continuous teacher training are critical to the successful implementation of EMI. Students benefiting from these measures are more likely to achieve academic and emotional success while developing greater proficiency in English. By adopting such approaches, private schools in the Chilaw area can maximize the advantages of EMI, creating an education system that is globally competitive yet culturally grounded. Ultimately, the study emphasizes the importance of equipping learners with the knowledge and skills necessary to thrive in an increasingly interconnected world while maintaining strong cultural ties.
Keywords: Private schools; Primary education; Parents; Students; Teachers; EMI